White‐Fluorescent Dual‐Emission Mechanosensitive Membrane Probes that Function by Bending Rather than Twisting. (20th June 2018) - Humeniuk, Heorhii V.; Rosspeintner, Arnulf; Licari, Giuseppe; Kilin, Vasyl; Bonacina, Luigi; Vauthey, Eric; Sakai, Naomi; Matile, Stefan
Abstract: Bent N, N′‐diphenyl‐dihydrodibenzo[a, c]phenazine amphiphiles are introduced as mechanosensitive membrane probes that operate by an unprecedented mechanism, namely, unbending in the excited state as opposed to the previously reported untwisting in the ground and twisting in the excited state. Their dual emission from bent or "closed" and planarized or "open" excited states is shown to discriminate between micelles in water and monomers in solid‐ordered (So ), liquid‐disordered (Ld ) and bulk membranes. The dual‐emission spectra cover enough of the visible range to produce vesicles that emit white light with ratiometrically encoded information. Strategies to improve the bent mechanophores with expanded π systems and auxochromes are reported, and compatibility with imaging of membrane domains in giant unilamellar vesicles by two‐photon excitation fluorescence (TPEF) microscopy is demonstrated.